In situ scanning tunneling microscopy study of Ca-modified rutile TiO2(110) in bulk water - Serrano, Giulia; Bonanni, Beatrice; Kosmala, Tomasz; Di Giovannantonio, Marco; Diebold, Ulrike; Wandelt, Klaus; Goletti, Claudio (Beilstein Journal of Nanotechnology, 2015)
Despite the rising technological interest in the use of calcium-modified TiO2 surfaces in biomedical implants, the Ca/TiO2 interface has not been studied in an aqueous environment. This investigation is the first report on the use of in situ scanning tunneling microscopy (STM) to study calcium-modified rutile TiO2(110) surfaces immersed in high purity water. The TiO2 surface was prepared under ultrahigh vacuum (UHV) with repeated sputtering/annealing cycles. Low energy electron diffraction (LEED) analysis shows a pattern typical for the surface segregation of calcium, which is present as an impurity on the TiO2 bulk. In situ STM images of the surface in bulk water exhibit one-dimensional rows of segregated calcium regularly aligned with the [001] crystal direction. The in situ-characterized morphology and structure of this Ca-modified TiO2 surface are discussed and compared with UHV-STM results from the literature. Prolonged immersion (two days) in the liquid leads to degradation of the overlayer, resulting in a disordered surface. X-ray photoelectron spectroscopy, performed after immersion in water, confirms the presence of calcium.
Keywords: alkali earth metals; scanning probe microscopy; solid/liquid interface; titanium dioxide reconstruction